Reliability and validity of the Brazilian version of the HSOPSC: a reassessment study - Cláudia Tartaglia Reis; Josué Laguardia; Cláudia Garcia de Barros; Paola Bruno de Araujo Andreoli; Mônica Martins
Abstract: This study aimed to reassess the psychometric properties of the Hospital Survey on Patient Safety Culture (HSOPSC) adapted to Portuguese for use in the Brazilian context. An observational, cross-sectional study was performed in a large, private, non-profit, acute care hospital, reference in patient safety, in a major Brazilian metropolis. Participants were selected from a non-probability sample of all eligible personnel in the various hospital departments invited to participate in the study. Reliability of the HSOPSC was assessed by estimating Cronbach's alpha for each dimension. confirmatory factor analysis (CFA), a matrix of correlations between the dimensions, and exploratory structural equation modelling (ESEM) were used in exploratory and confirmatory analyses of the structural validity of the construct. The overall response rate was 18.7% (n = 1,439). Four dimensions ("overall perceptions of patient safety"; "staffing"; "teamwork across units"; and "non-punitive response to error") returned problems of internal consistency. CFA returned acceptable fit with the original 12-dimension model. Correlations between the dimensions of the original 12-dimension model indicated discriminant validity problems, while residual variance was greater than 0.70 in 13 items. The ESEM of the original 12-dimension model returned good fit, with the following indices: CFI = 0.985; TLI = 0.968, and RMSEA = 0.026 (90%CI: 0.024-0.029). Although better than those of the first evaluation, the results obtained in this validity and reliability reassessment of the Brazilian version of the HSOPSC require further research.